Description of The Learning Motivation of 10th Grade High School Students in Chemistry Learning on The Merdeka Curriculum Application - Amara, Shandy Mahyidien; Hairida,; Erlina, (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Learning motivation is an important factor that influences student success in the learning process. This study aims to describe the level of learning motivation of tenth grade students in Chemistry using the Merdeka Curriculum. This study uses a quantitative descriptive approach with 143 tenth grade students at Mujahidin High School in Pontianak as subjects. Data collection techniques included observation, questionnaires, and documentation, while data analysis was conducted descriptively by calculating the percentage of each learning motivation indicator. The results showed that students' learning motivation was in the high category, with details as follows: desire and willingness to succeed (74%), hopes and future aspirations (63%), showing interest (62%), perseverance in completing tasks (74%), appreciation in the learning process (63%), interesting learning activities (50%), a conducive learning environment (77%), and encouragement and needs in learning (65%). Overall, student motivation is classified as high, but the indicator of interesting learning activities still needs improvement. These findings are recommended to schools and teachers as a basis for providing supporting facilities, designing instructional designs, and implementing more varied learning strategies to increase student learning motivation.